2021
DOI: 10.1055/a-1326-1792
|View full text |Cite
|
Sign up to set email alerts
|

Decision Aids for Preventive Treatment Alternatives for BRCA1/2 Mutation Carriers: a Systematic Review

Abstract: Introduction Women with a pathogenic BRCA1/2 mutation have a markedly increased lifetime risk of developing breast and/or ovarian cancer. The current preventive treatment alternatives that are offered are an intensified breast cancer screening programme and risk-reducing operations. Before deciding on one option, medical and personal factors such as life situation and individual preferences must be weighed carefully. Decision aids are used internationally to support BRCA1/2 mutation carriers during their decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Participants requested lectures on risk communication and preference‐sensitive decision‐making (Kautz‐Freimuth et al., 2022; Krassuski et al., 2021; Stracke et al., 2022). These clinical case presentations addressing contralateral BC risk and competing risk factors received very high ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Participants requested lectures on risk communication and preference‐sensitive decision‐making (Kautz‐Freimuth et al., 2022; Krassuski et al., 2021; Stracke et al., 2022). These clinical case presentations addressing contralateral BC risk and competing risk factors received very high ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Undecided individuals might appreciate additional support, to explore readiness for risk reducing surgery before the next step of making an appointment at the HGC, such as engaging with a decision-aid (Culver et al, 2011;Harmsen et al, 2018;Krassuski et al, 2021). et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Undecided individuals might appreciate additional support, to explore readiness for risk reducing surgery before the next step of making an appointment at the HGC, such as engaging with a decision‐aid (Culver et al, 2011; Harmsen et al, 2018; Krassuski et al, 2021). For example, Culver et al (2011) designed a web‐based aid as an adjunct to genetic counselling, which includes a values and preferences exercise to help individuals learn whether they are “decided” or “undecided.” Participants rank contextual factors, such as cancer risk, cancer worry, fertility and family planning and surgical outcomes, and then receive information and recommended next steps.…”
Section: Discussionmentioning
confidence: 99%
“…In order to support BRCA1/2 mutation carriers during their complex decision-making process in choosing a preventive option and the right time to do so, a number of supportive tools, in particular, decision aids (DAs), have been developed internationally [30][31][32][33][34][35][36]. A systematic review on DAs for women with BRCA1/2 mutations identified four RCTs and one pretest-post-test study that assessed the effectiveness of DAs on decision-, knowledge-and health-related criteria.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%